Chemical kinetic measurements of a mammalian acetylcholine receptor by a fast-reaction technique. - Udgaonkar, J B (1987)
In the presence of acetylcholine, the nicotinic acetylcholine receptor undergoes two rapid conformational changes: one in the 1-ms time region, leading to the formation of a transmembrane channel and signal transmission between cells, and the other in the 100-ms time region, leading to an inactive "desensitized" form with altered ligand-binding properties. To determine the properties of the receptor that are relevant for channel opening and signal transmission, we have developed a cell-flow technique that allows measurements to be made with cells prior to receptor desensitization. Here we illustrate the usefulness of the technique. A wide concentration range of both a ligand that controls the opening of receptor channels (carbamoylcholine) and a receptor inhibitor (procaine) was used to measure the dissociation constant of the receptor site controlling channel opening (2.4 X 10(-4) M), the channel-opening equilibrium constant (5.5), the inhibition constant for procaine (5.8 X 10(-5) M), and the rate coefficients for two desensitization processes of 5 s-1 and 0.2 s-1. The cell-flow technique illustrated here is of interest because, by rapid-reaction techniques, it extends the chemical kinetic approach from investigations of reactions in solutions to investigations of many different receptors that exist in membranes of central nervous system cells and whose properties are not well known.